Капка сьӧрын - Емельянов Константин Васильевич (Удмуртия, 1995)
Экземпляры: (20240112) / Инвентарный номер: 23898 / Цена: 4800.00 / Сис.шифр: 84(2=664.1Удм) / Авт.знак: Е 60 / ГРНТИ: 17.82 / ББК: 84(2=664.1Удм)